Reliance Industries launches Mission Oxygen - Reliance Industries Limited (2022)
Starting from zero before the pandemic, Reliance Industries has now become India’s largest producer of medical grade liquid oxygen from a single location, producing over 1,100 MT of medical oxygen per day.